The Silphinae (Staphylinidae) and Agyrtidae of Kentucky with an illustrated key to the fauna of eastern North America - Chapman, Eric G.; Clarkson, Melissa D; Wright, Charles E; Dupuis, Julian R. (Zootaxa, 2026)
The carrion beetle fauna (Staphylinidae: Silphinae) of eastern North America has seen some recent changes and additions in the past decade. Two species of Silpha have been introduced and have become established and Nicrophorus vespilloides was discovered to be two species. In this paper, we present a fully illustrated key to the Silphinae of eastern North America (U.S. states entirely east of the Mississippi River and Canadian provinces east of the Ontario-Manitoba border) that reflects these faunal changes. We focus on the silphine fauna of Kentucky and include the single species of Agyrtidae (primitive carrion beetles), as common sampling methods will often pick up members of both groups. We include 22 species of Silphinae and one species of Agyrtidae in our key, and we report one species of Agyrtidae and 11 species of Silphinae from Kentucky, including one new state record (Nicrophorus defodiens). We present the following information for each eastern North American species in an annotated list: diagnostic characters, recent taxonomic changes (if applicable), life history information and more detailed information for Kentucky species including counties, collecting years and months, collections housing the specimens, and collecting methods. Distribution maps for Kentucky specimens are presented. Using this dataset, the bias-corrected iChao2 species richness estimator predicted that 12 species should be found in Kentucky, indicating that our sampling is likely complete.